Does physical activity, eating habit and psychological stress affect body mass index? A cross-sectional study among university students in Malaysia - Mehrnoosh Akhtari-Zavare; Sherina Mohd Sidik; Nurul Elyani Mohamad; Nurfaizah Saibul (Universiti Putra Malaysia, 2025)
Being overweight or underweight can take its toll on health. The trends in body mass index (BMI), especially higher BMI, has become a significant concern, not only in Malaysia but worldwide. This study seeks to investigate how far do physical activity, eating habit and psychological factors affect the BMI among university students in Malaysia. Materials and methods: A data of university students aged 18 years old and above were collected throughout Malaysia (n=1821) using a self-administered, dual-language survey questionnaire. BMI (kg/m2) was a dependent variable in multiple linear regression models with sociodemographic, academic, psychosocial, eating habits and physical activity characteristics as its independent variables. Results: The prevalence of underweight, overweight and obesity among the university students were 15.9%, 17.5% and 7.9%, respectively. There was a significant relationship found between BMI and gender, age, ethnicity, residency, parents with tertiary education, level of education, academic year, the field of study, current living arrangements, depression, anxiety, water intake, vegetable intake, snacking frequency, and recreation factors. This study confirmed the association be- tween physical activity, eating habit and psychological stress with BMI. Implementing appropriate interventions on the importance of healthy BMI is crucial to create awareness among the students in order to lead them towards a healthy lifestyle.